Study of Serum Adiponectin, Leptin, and Galectin-3 in Breast Cancer - Abdulkareem Ibrahim, Aisha; Nori Ahmed , Sardar (Diyala Journal of Medicine, 2023)
Background: Breast cancer is the most common cancer that threatens the lives of women all over the world. Adipocytokines (adiponectin, leptin), and the β-galactoside-binding proteins (galectin-3) are new suggested parameters for the diagnosis and prognosis of breast cancer. Objective: To find relationship between serum adiponectin, leptin, and galectin-3 and breast cancer diagnosis and prognosis factors. Patients and Methods: A case-control study was done between (August 2021 to June 2022). Totally collected 111 female blood samples from patients that diagnosed with a breast cancer and healthy control, Samples were grouped into Group I (30 healthy control), Group II (43 patients pre-treatment), and Group III (38 patients post-treatment), from Rizgary Teaching Hospital, Nanakali Hospital, Hawler Teaching Hospital- General surgery and Neurosurgical Department, PAR Private Hospital, PAKY Hospital, and Rasul Private Hospital at Iraq-Erbil city and the age 18 up to 77 included in this study. Biochemical tests were performed (Adiponectin, Leptin, Galectin-3). These sample were analysed by using blood serum, statistically analysis the result. Results: The post-treatment, pre-treatment, and control in respectively about (60.52%, 60.46%, and 63.34%) were the majority of the study population (38-57) age group. There is a statistically significant differences between case and control groups in residency, family history, and BMI with a P-vale of (0.08, <0.001, 0.015), respectively. Leptin, adiponectin, and galectin-3 were statistically significant (0.007, <0.01, and <0.01), in respectively. About cancer characteristic galectin-3 was significant with (ER/PR) receptor (P:0.037) and grade (P:0.034), also leptin was significant with the grade (P: 0.025). Conclusion: We concluded that Adiponectin, Leptin, and Galectin-3 were new potential biochemical marker for diagnosis and prognosis the breast cancer, would be useful and important marker for assessing and evaluating grad, and receptor of the therapy plan.